Sonic anemometer and atmospheric flows over complex terrain: measurements of complex flows - Ribeiro, Luis Frölén (2014)
Three measurement campaigns and the use of sonic anemometry under specific conditions are described in this work. EBEX2000 was an international energy balance field experiment in San Joaquin Valley USA, were different sonic anemometer types, and heat and momentum flux measurements, were analyzed and compared. The second case was a complex coastal flow at Madeira Island, Portugal. The complexity of the flow compromised the performance of an existing wind farm. The use of post-processing techniques, such as Fourier and wavelet spectral analysis allowed the detection, and unveiled, the existence of coherent structures and other specific features of that wind turbine site. The flow over the mountainous terrain of Madeira Island is also presented for the latter case, where sonic anemometer measurements were executed at wind energy resource assessment phase.